Bubrežni tumori u detinjstvu - pregledni članak - Vujanić, Gordan M; Đuričić, Slaviša M (Scripta Medica, 2022)
Renal tumours of childhood are rare, although they are one of the most common solid tumours in children. They include numerous entities, which have different clinical, histological, molecular biological and prognostic features, so their precise diagnosis and staging are critical for appropriate treatment. The most common is Wilms’ tumour (WT) with 80-85 % of all cases, whereas other entities including mesoblastic nephroma, clear cell sarcoma, rhabdoid tumour, renal cell carcinoma, metanephric tumours and others are very rare (2-4 % each) which explains why they represent a big diagnostic challenge for diagnostic pathologists. They are subclassified into three risk groups – low, intermediate and high – which have different treatments and prognosis. There are two big study groups which have different approaches but remarkable similar outcomes. The International Society of Paediatric Oncology approach (followed in most of the world) is based on preoperative chemotherapy, followed by surgery and further therapy, whereas the Children’s Oncology Group approach (followed mainly in the United States and Canada) is based on primary surgery, followed by postoperative treatment.